Robot Layanan Cerdas All-in-One untuk Lingkungan Serbaguna - Abd Eltwab, Ahmed Aly (JURNAL MECHANICAL, 2025)
ABSTRACT – The Multi-Functional Cleaner Robot can effectively complete a variety of domestic cleaning jobs, doing away with the need for many specialized tools because of its adaptable design,. It is capable of precise surface navigation because to its sophisticated sensors and clever algorithms. It can clean confined areas like corners and beneath furniture because of its small size and excellent movement. One of the robot's primary features is a robotic arm that can precisely grasp and raise objects off the ground. Stable object manipulation is ensured by precise end-effector movement and seamless joint coordination. The system adjusts to various object forms and placements by using real-time tactile and visual input. The mobility and handling performance of the robot are optimized using methods such as feedback control and inverse kinematics. As a result, it can efficiently complete operations like picking, sorting, and positioning. The robot greatly lessens the need for humans to do repetitive cleaning tasks. It also has sophisticated safety features to guarantee dependable functioning